2015
DOI: 10.1179/1607845415y.0000000039
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with 5-Azacytidine improves clinical outcome in high-risk MDS patients in the ‘real life’ setting: A single center observational study

Abstract: In conclusion, 5-AZA is an effective treatment for high-risk MDS. Improved OS and EFS were found mainly in patients who responded to the treatment while ΔWPSS seems to represent a promising future prognostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Moreover, the expression of a splice variant could be combined with clinical markers; for instance, the expression of BCL2L12 splice variant 1 and BCL2 variant alpha in malignant B cells of patients with chronic lymphocytic leukemia could be combined with lymphocyte count and/or other clinical features to provide a better prognostic system than the currently used ones (48,52). Similarly, expression of important transcripts resulting from alternative splicing in blasts of patients with myelodysplastic syndromes could be used along with novel markers such as monosomal karyotype to predict prognosis (53), treatment decision-making (54), or patients' response to therapy (55,56), at is has recently been proposed. Distinct 3'-untranslated regions (3'-UTRs) of splice variants of a single protein-coding gene resulting from alternative splicing may have other implications, including different regulatory properties.…”
Section: Biological and Clinical Significance Of Splice Variantsmentioning
confidence: 99%
“…Moreover, the expression of a splice variant could be combined with clinical markers; for instance, the expression of BCL2L12 splice variant 1 and BCL2 variant alpha in malignant B cells of patients with chronic lymphocytic leukemia could be combined with lymphocyte count and/or other clinical features to provide a better prognostic system than the currently used ones (48,52). Similarly, expression of important transcripts resulting from alternative splicing in blasts of patients with myelodysplastic syndromes could be used along with novel markers such as monosomal karyotype to predict prognosis (53), treatment decision-making (54), or patients' response to therapy (55,56), at is has recently been proposed. Distinct 3'-untranslated regions (3'-UTRs) of splice variants of a single protein-coding gene resulting from alternative splicing may have other implications, including different regulatory properties.…”
Section: Biological and Clinical Significance Of Splice Variantsmentioning
confidence: 99%
“…), permitting their easy quantification paving the way for the development of non-invasive assays in the era of personalized medicine (84,85). Moreover, proteins that are targeted by important miRNAs could also participate in such multiparametric panels of biomarkers (86)(87)(88)(89), along with clinical markers (90)(91)(92). tRFs tRFs constitute novel sncRNA molecules generated by specific cleavage of tRNA transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with intermediate‐2 and high‐risk MDS have poor prognosis and increased risk of transformation to AML. 5‐AZA is 1 of the first‐line treatment options for this group of patients, and both clinical trials and real‐world data have demonstrated improved clinical outcome for patients responding to 5‐AZA . However, there is a group of patients who have SD as BR.…”
Section: Discussionmentioning
confidence: 99%
“…cal trials (AZA 001) and in the real-life setting. 5,6 According to the AZA 001 study, this impact on survival was observed in 5-AZA-treated patients despite the relatively low response rates of 29% (complete remission (CR) 17% and partial remission (PR) 12%). 7 The median number of cycles required to achieve initial response (IR) was 3, while 81% of patients needed up to 6 cycles and 90% of patients needed up to 9 cycles to reach their IR.…”
mentioning
confidence: 99%